WASATHIYYAH dalam AL-QUR’AN PERSPEKTIF QURAISH SHIHAB GUNA MENUMBUHKAN SIKAP TOLERANSI - Sukirno Sukirno; Umar Badruzzaman; Ade Naelul Huda (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The Indonesian nation is a country that has uniqueness with the diversity of tribes, races, customs, languages, traditions, cultures, beliefs and faiths so that they can blend and unite in the ideology of Pancasila. This greatest gift is an extraordinary potential that we must be grateful for by maintaining and caring for it. Silaturrahmi is an important concept in various religions that emphasizes the importance of maintaining good relations with fellow human beings. In the context of religious moderation, silaturrahmi is a strong foundation for building harmony and tolerance between religious communities. The aim is to analyze the word 'silaturrahmi' in the Qur'an using the wasathiyyah (moderation) approach method of Quraish Shihab. The method used is library-research-descriptive. Data presentation is taken from the text of the Qur'an and related literature that discusses the theory of wasathiyyah Quraish Shihab. The analysis was conducted by identifying the meaning of ghuluw (extremism) and why wasathiyyah is a means of silaturrahmi and the main steps to realize wasathiyyah. The analysis shows that the word silaturrahmi is not only formed from Muslim circles alone, but can also lead to religious moderation. While each individual can understand and appreciate the differences in beliefs and religious practices of others, it will create a harmonious and peaceful environment. Quraish Shihab's wasathiyyah approach will present broad insights into the understanding of silaturrahmi in the Qur'an, not only in terms of linguistics but also leading to socio-culture.